ANALISIS KEUNTUNGAN USAHA KEDAI KOPI â€œBABA BUDANâ€ JALAN RODA DI KOTA MANADO - William Marcel Tanwijaya; Ribka Magdalena Kumaat; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2018)
This study aims to analyze the profitability of the coffee shop business "Baba Budan" so that it can be known in detail the amount of profit each month earned business coffee shop "Baba Budan" in the culinary area on the wheel road in Manado City. Data used in this study primary data obtained by conducting direct interviews with business owners using questionnaires, and secondary data obtained from literature studies in the form of literature, written sources or documents that have relevance to this research. Data analysis method used is descriptive analysis, using business profit analysis, then continued with analysis of Return of Cost Ratio, then presented in table form. The results of this study indicate that the business coffee shop "Baba Budan" gives monthly profit of Rp. 4.208.028,2, with R / C ratio of 1,45. So it can be concluded that the culinary business is a profit to run because the value of R / C more than 1. This shows that every Rp. 1 production costs incurred by coffee shop owners are able to provide cash in the form of revenue of Rp. 1,45. Where the total revenue is still greater than the total cost of production and this business for each month.